The Constitutionality of Appointment of Acting Regional Heads in Constitutional Court Judgment - Ahmad Siboy; Muhammad Nur (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Purpose of the study: This research aimed to describe the ratio decindi of the Constitutional Court's judgment in terms of judicial review regarding the appointment of acting regional heads and its implications on the meaning of sovereignty in its implementation. Methodology: This research is normative legal research because it is based on the Constitutional Court Judgment Number 67/PUU-XIX/2021. The approaches used are the statutory regulations approach, the judge's decisoon approach, the conceptual approach, the case approach, and the philosophical approach. Results: The Constitutional Court stated that the appointment of acting regional heads as a result of the postponement of the Pilkada was a legal policy chosen by the legislators (People's Representative Council and President) which qualified as a constitutional legal alternative considering that the delay of the Pilkada had no impact on reducing the right to vote and the right to be candidate. Applications of this study: This research can be used to develop courses in general election law and regional head elections, especially in understanding how the Constitutional Court considers a decision. Apart from that, this research can also be used as a consideration in efforts to change the law regarding regional elections or can also be used as additional evidence if another judicial review of the regulations regarding the postponement of regional elections. Novelty/ Orginalty of this study: There has been no previous research that specifically analyzes the Constitutional Court's judgment regarding the appointment of acting regional heads in terms of the legitimacy of the meaning of popular sovereignty and its implications for the practice of appointing acting regional heads. The legitimacy of the appointment of acting regional heads in the Constitutional Court’s judgment is an interpretation that has degrade the challenge of the meaning or position of regional heads, in which the status has experienced shifting in meaning from a political position to a career position. As a result, the people's right to determine their own regional heads is taken over by the central government. The shift from the people's right to choose to the right of the President and Ministers to appoint regional heads is a shift that leads to a shift in sovereignty, namely, from the sovereignty of the people to the sovereignty of the ruler. Keywords: Regional head, Ratio decidendi, Popular sovereignty. ABSTRAK Tujuan: Penelitian ini bertujuan untuk menguraikan ratio decindi putusan MK dalam hal uji materi tentang penunjukkan penjabat kepala daerah serta implikasinya terhadap makna kedaulatan rakyat dalam implementasi penunjukkan kepala daerah. Metodologi: Penelitian ini termasuk dalam jenis penelitian yuridis normatif karena berpijak pada putusan Mahkamah Konstitusi Nomor 67/PUU-XIX/2021. Pendekatan yang digunakan adalah pendekatan peraturan perundang-undangan, pendekatan putusan hakim, pendekatan konsep, pendakatan kasus dan pendekatan filosofis. Temuan: Mahkamah Konstitusi menyatakan bahwa penunjukkan penjabat kepala daerah sebagai akibat dari penundaan penyelenggaraan Pilkada merupakan politik hukum yang dipilih pembentuk undang-undang (DPR dan Presiden) yang terkualifikasi sebagai pilihan hukum yang konstitusional mengingat penundaan Pilkada tersebut tidak berdampak terhadap pengurangan hak untuk dipilih (right to vote) dan hak untuk memilih (right tobe candidate). Kegunaan: Penelitian ini dapat dimanfaatkan bagi pengembangan mata kuliah hukum pemilihan umum dan pemilihan kepala daerah khususnya hal mengetahui bagaimana MK membuat pertimbangan dalam suatu putusan. Disamping itu, penelitian ini juga dapat dijadikan pertimbangan dalam upaya perubahan undang-undang tentang Pilkada atau dapat pula dijadikan sebagai tambahan dalil apabila akan dilakukan uji materi lagi terhadap aturan tentang penundaan Pilkada. Kebaruan/Orisinalitas: Belum terdapat penelitian terdahulu yang menganalisis secara khusus putusan Mahkamah Konstitusi tentang penunjukkan penjabat kepala daerah dari sisi legitimasi makna kedaulatan rakyat dan implikasinya dalam praktek penunjukkan penjabat kepala daerah. Legitimasi penunjukkan penjabat kepala daerah dalam putusan Mahkamah konstitusi merupakan tafsir yang telah mereduksi tantang makna atau kedudukan kepala daerah dimana kedudukan kepala daerah mengalami pergeseran makna dari jabatan politis menjadi jabatan karir. Akibatnya, hak rakyat untuk menentukan sendiri kepala daerahnya diambil alih oleh pemerintah pusat. Pergeseran hak untuk memilih dari rakyat secara langsung menjadi hak Presiden dan Menteri dalam hal penunjukkan kepala daerah merupakan pergeseran yang menyebabkan terjadinya peralihan kedaulatan. Yakni, dari kedaulatan rakyat menjadi kedaulatan penguasa. Keywords: Penjabat kepala daerah, ratio decidendi, Kedaulatan Rakyat.